Analysis of Capital Asset Pricing Model (CAPM) as a Basis for Investing in Stocks (Case Study on the Banking Sub-Sector of the Business Index-27 in the 2022 IDX) - Idrus, Muhammad Islah (International Journal of Artificial Intelligence Research, 2024)
This study aims to analyze optimal investment options in the banking sub-sector in the Bisnis-27 Index on the Indonesia Stock Exchange (IDX) in 2022, using  the Capital Asset Pricing Model (CAPM) approach. Stock movement, risk, and return data were analyzed from 2020 to 2022 to illustrate capital market dynamics related to the impact of the COVID-19 pandemic and global economic factors.This quantitative descriptive research is to provide an accurate and systematic picture of stock returns and the systematic risks of the banking subsector in the Business-27 Index for 2022. All companies that are part of the Bisnis-27 Index and traded on the Indonesia Stock Exchange during that time period constitute the research population. This study uses the Capital Asset Pricing Model (CAPM) to evaluate investments by determining the potential returns and risks associated with stocks. To determine the systematic risk of an investment, we use Microsoft Excel to perform calculations including collecting data on the closing price of a stock, estimating market yields and yields, and calculating the beta coefficient.The results show that Bank Negara Indonesia and Bank Mandiri are among the efficient stocks, while Bank Central Asia and Bank Rakyat Indonesia are among the inefficient stocks. These findings provide valuable guidance for investors in making investment decisions based on stock efficiency and associated risks